IL-1β Promotes Staphylococcus aureus Biofilms on Implants in vivo - Gutierrez Jauregui, Rodrigo; Fleige, Henrike; Bubke, Anja; Rohde, Manfred; Weiss, Siegfried; Förster, Reinhold (Frontiers in Immunology, 2019)
Implant associated infections represent a serious health burden in clinics since some microorganisms are able to colonize biological surfaces or surfaces of indwelling medical devices and form biofilms. Biofilms represent communities of microorganisms attached to hydrated surfaces and enclosed in self-produced extracellular matrix. This renders them resistant to exogenous assaults like antibiotics or immune effector mechanisms. Little is known regarding the role of the immune system in the formation of biofilms during implant associated infections, largely due to the lack of suitable mouse models. Here we use colonized osmotic pumps in mice to study the interaction of an activated immune system with biofilm-forming Staphylococcus aureus encoding Gaussia luciferase. This approach permits biofilm formation on the osmotic pumps in living animals. It also allows the continuous supply of soluble immune cell activating agents such as cytokines to study their effect on biofilm formation in vivo. Using noninvasive imaging of the bioluminescent signal emitted by the lux expressing bacteria for quantification of bacterial load in conjunction with light and electron microscopy, we observed that pump-supplied pro-inflammatory cytokine IL-1b strongly increased biofilm formation along with a massive influx of neutrophils adjacent to the biofilm-coated pumps. Thus our data demonstrate that immune defense mechanisms can augment biofilm formation.